2015
DOI: 10.3389/fncel.2015.00366
|View full text |Cite
|
Sign up to set email alerts
|

CD36 is involved in oleic acid detection by the murine olfactory system

Abstract: Olfactory signals influence food intake in a variety of species. To maximize the chances of finding a source of calories, an animal’s preference for fatty foods and triglycerides already becomes apparent during olfactory food search behavior. However, the molecular identity of both receptors and ligands mediating olfactory-dependent fatty acid recognition are, so far, undescribed. We here describe that a subset of olfactory sensory neurons expresses the fatty acid receptor CD36 and demonstrate a receptor-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 74 publications
4
24
0
Order By: Relevance
“…It is therefore possible that CD36-dependent recognition of volatile compounds, including Z,Z-TDD, on the olfactory surface is much more effective than expected. Indeed, olfactory sensory neurons of mice were shown to respond to a low nanomolar level of oleic acid by a mechanism involving this receptor (18). In addition, we have found that a low micromolar level of KOdiA-PC is perceived in mice via a mechanism requiring CD36 (15).…”
Section: An Assessment Of the Inhibition Pattern Of Zz-tdd For Afl-omentioning
confidence: 72%
See 1 more Smart Citation
“…It is therefore possible that CD36-dependent recognition of volatile compounds, including Z,Z-TDD, on the olfactory surface is much more effective than expected. Indeed, olfactory sensory neurons of mice were shown to respond to a low nanomolar level of oleic acid by a mechanism involving this receptor (18). In addition, we have found that a low micromolar level of KOdiA-PC is perceived in mice via a mechanism requiring CD36 (15).…”
Section: An Assessment Of the Inhibition Pattern Of Zz-tdd For Afl-omentioning
confidence: 72%
“…On the basis of gas chromatography, the puriimportant for interactions with the binding site (5). Recently, we and others have demonstrated that CD36 is produced by distinct types of olfactory sensory neurons and is abundantly present on the surface of the olfactory epithelium (i.e., on the ciliary layer) in mice (14,18,31). In addition, another series of studies using Drosophila melanogaster have illustrated that a sensory neuron membrane protein, a CD36 homolog in the insect, localizes on the dendrites of specific olfactory neurons to mediate sensing of volatile pheromones, including (Z)-11-octadecenyl acetate (3,6).…”
Section: Preparation Of Test Compoundsmentioning
confidence: 99%
“…A novel finding of our studies using the CD36 peptides was that aliphatic aldehydes such as tetradecanal, a distinct class of volatile odorants, were capable of inhibiting fl-oxLDL binding to the mimics (i.e., were identified as potential CD36 ligands) (32,33,35). Furthermore, others and we have discovered that CD36 is expressed by a population of olfactory sensory neurons and is abundantly present in the olfactory ciliary layer in mice (17,22,38). These recent findings led us to propose that CD36 participates in the capture and detection of specific odorants in the nasal cavity of mammals.…”
Section: Preparation Of Mimic Peptides For Class B Scavengermentioning
confidence: 83%
“…S1) are sufficient for hydrophobic interaction in the recognition of these aliphatic aldehydes. CD36 is produced by a population of olfactory sensory neurons, and is transported to and accumulates in the cilia, the first line for olfactory percep-tion of odorants (17,22,38). The most likely role of the receptor at this site has been postulated to serve as an obligate transmembrane partner for G-protein-coupled odorant receptors, facilitating the recognition of specific odorants (4,12,38).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, a vessel containing a sheet of filter recent studies demonstrated a novel role of CD36-the role in the olfactory system. This is exemplified by (i) the localisation of the receptor on the cilia of olfactory sensory neurons in the murine main olfactory epithelium (19), (ii) a weaker response to oleic acid in the olfactory sensory neurons of CD36-knockout mice compared with their wild-type littermates (21) and (iii) a reduction of preference for a lipid mixture odour through dysfunction of CD36 in mice (29). However, there have been no acoustic and ethological analyses of mammalian behaviour addressing the involvement of CD36 in the olfactory perception of specific odour-active volatile compounds.…”
mentioning
confidence: 99%